Coffee consumption and its interaction with the genetic variant AhR rs2066853 in colorectal cancer risk: a case–control study in Korea. (31st January 2022) - Lu, Y-Thanh; Gunathilake, Madhawa; Lee, Jeonghee; Kim, Youngyo; Oh, Jae Hwan; Chang, Hee Jin; Sohn, Dae Kyung; Shin, Aesun; Kim, Jeongseon
Abstract: The bioactive compounds in coffee have several antioxidant properties that may beneficially impact colorectal cancer (CRC) development. The aryl hydrocarbon receptor (AhR) is an important transcription factor that regulates an enzyme related to the caffeine metabolism pathway. We investigated the modification effect on coffee of AhR gene polymorphism in the risk of CRC. A case–control study was conducted with 699 cases and 1393 controls to investigate the interaction between coffee intake and the AhR rs2066853 variant in CRC risk. The odds ratios (ORs) and 95% confidence intervals (CIs) were assessed using multiple logistic regression analyses. We observed a significant protective effect of coffee against CRC in the overall and male populations. Consuming three or more cups of coffee per day may significantly lower CRC risk in all subjects by 77% and in men by 83% (OR = 0.23, 95% CI: 0.14–0.39 and OR = 0.17, 95% CI: 0.09–0.34, respectively, P- trends < 0.001). No association between AhR rs2066853 and CRC risk was found. In the dominant model, the G/G genotype had a strongest synergistic effect with coffee on protection against CRC (OR = 0.12, 95% CI: 0.06–0.26, P- interaction = 0.014). The interaction remained significant in men and the distal colon cancer subgroup. In the additive model, the interaction was clearly shown strongest in G/G carriers (OR = 0.12, 95% CI: 0.06–0.27, P -interaction = 0.039), followed by A/A and G/A carriers. The interaction remained significant in men and the rectal cancer subgroup. In conclusion, the protective effect of coffee on CRC risk might interact with the genetic variant AhR rs2066853, and this joint effect was determined by sex and site-specific cancer. Graphical Abstract: